2014
DOI: 10.1016/j.cub.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Cytoskeleton, NET3C, and VAP27 Mediate the Link between the Plasma Membrane and Endoplasmic Reticulum

Abstract: The cortical endoplasmic reticulum (ER) network in plants is a highly dynamic structure, and it contacts the plasma membrane (PM) at ER-PM anchor/contact sites. These sites are known to be essential for communication between the ER and PM for lipid transport, calcium influx, and ER morphology in mammalian and fungal cells. The nature of these contact sites is unknown in plants, and here, we have identified a complex that forms this bridge. This complex includes (1) NET3C, which belongs to a plant-specific supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
220
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(259 citation statements)
references
References 31 publications
22
220
1
1
Order By: Relevance
“…FRAP and time-lapse experiments showed that these structures were remarkably stationary, providing a clear distinction between the pools of highly dynamic intracellular SYT1 and stable cortical SYT1. Interestingly, a previous study has shown that VAP27 and NET3C associate tightly to the cortical MTs and F-actin cables, directly connecting the ER to the cortical cytoskeleton at ER-PM contact sites (Wang et al, 2014). Our data support and expand this view and suggest that the cortical tubulin cytoskeleton also provides positional cues for the establishment of ER-PM contact sites.…”
Section: Syt1 Anchors the Pm At Mt-depleted Regionssupporting
confidence: 79%
See 4 more Smart Citations
“…FRAP and time-lapse experiments showed that these structures were remarkably stationary, providing a clear distinction between the pools of highly dynamic intracellular SYT1 and stable cortical SYT1. Interestingly, a previous study has shown that VAP27 and NET3C associate tightly to the cortical MTs and F-actin cables, directly connecting the ER to the cortical cytoskeleton at ER-PM contact sites (Wang et al, 2014). Our data support and expand this view and suggest that the cortical tubulin cytoskeleton also provides positional cues for the establishment of ER-PM contact sites.…”
Section: Syt1 Anchors the Pm At Mt-depleted Regionssupporting
confidence: 79%
“…2B). Since the SYT1 localization at the ER-PM interface strongly resembled that of the recently reported Arabidopsis VAP27 and NET3C ER-PM markers (Wang et al, 2014), we next performed transient colocalization studies using the RFP-tagged VAP27 fused to the Ubiquitin-10 promoter (UBQ10proVAP27-RFP) and SYT1proSYT1-GFP markers in N. benthamiana leaves. As shown in Figure 2, C and D, the markers colocalized to a great extent in both intracellular and cortical regions of the cell.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations